Kuliner Pecel Madiun sebagai Bahan Ajar Bahasa Indonesia bagi Penutur Asing dalam Mendukung Internasionalisasi Kuliner Bahasa Indonesia - Aprilia Dwi Marlina; Fadhila Anna Gunawan; Johana Prastika Alfa; Musyaffa Izzul Haq; Kundharu Saddhono (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research will discuss the famous culinary dish, namely "Pecel Madiun", which will be used as new learning material for foreign students. The method used in this research is a qualitative descriptive approach, which aims to understand the condition of the research object as a whole in order to obtain detailed information about the creation of Indonesian language learning materials for Foreign Speakers (BIPA) using Madiun pecel as the context. This research also involved informants from one of the Madiun pecel food stall sellers in Jebres District, Surakarta City. The preparation of BIPA learning materials will be adjusted to the students' Indonesian language skills. Initial material will be presented in simple and easy to understand language, then more complex material will be introduced after students have mastered basic Indonesian. The choice of "Pecel Madiun" as the research object is very appropriate because this presents a new variation in BIPA Teaching Materials for foreign speakers.